Problems, Promises, and Paradoxes of Aid Africa's Experience - Ndulo, Muna (Cambridge Scholars Publishing, 2014)
farmers; introducing ethical and professional standards for civil service; and raising the competence of civil servants
Description based on publisher supplied metadata and other sources
Keywords: Wirtschaft; Africa -- Economic conditions; Africa -- Social conditions; Africa -- Social policy; Entwicklungshilfe; Effektivität; Afrika; Aufsatzsammlung